(untitled) (Journal of Pharmaceutical Negative Results, 2022)
The aim of the research is to synthesize cobalt oxide with Aleo vera and nickel oxide combined with turmeric extract, Curcuma longa. This study also compares them with the combined nanomaterials with Cinnamomum verum extract and Zingiber officinale extract characterize by Artificial roads nanoparticle and growth inhibition nanoparticles green synthesis method for Ecoli bacteria and Trichophyton mentagrophytes, Candida albicans and for each substance. Their properties were according to the two methods. The results found that all the NPs were nano-sized with good properties. According to the XRD tests, the results were observed in the drawing, in conformity with the global measurements and nanomaterials 37.02 (111, 44.6 200)), 62.5 (220). As for the SEM examination, the shapes of rocky, corky particles, Spherical and semi-spherical shapes in the form of scales or semi-crusts, and the particles appear size 25 nm TEM dimensions. The sizes of the nanoparticles range from 0.5-40 nm. The FTIR test for examining effective chemical bonds was between 500-4000 wavenumber (1/m). It was also found from the ZP examination that the material is not lumpy. The nickel oxide and cobalt oxide nanomaterials from the green synthesis method were more competent than the nanomaterials from the Artificial roads method in inhibiting E.Coli bacteria isolates. It is a concentration of (100) M%. Two nanocomposites were combined at a concentration of 0.1%M. The results showed that the Aloe vera with cobalt oxide solution and the ginger extract with nickel oxide solution, observed the average diameters of inhibition of bacterial growth for both of them (47) mm, which is more efficient than the extracts of other types of plants in inhibiting E.coli bacteria isolates. Here, the average inhibition diameters of the nanocomposites cobalt oxide solution with aloe vera and nickel oxide with turmeric extract were (29) mm, while the average inhibition diameters of the two nanocomposites, cobalt oxide solution with aloe vera and nickel oxide with ginger extract. Also, the average diameter of inhibition for bacterial growth (38) mm, when the average diameters of the inhibition of the nanomaterial were with the extract of the plant of the study, the results were not encouraging, and the nanomaterial did not appear in the tests encouragingly. The nickel and cobalt oxide solutions can influence significantly the growth of fungi in terms of inhibition, as it was found that there was no fungal growth Trichophyton mentagrophytes, and they also had impacts on the inhibition of fungal growth albicans. Nanosolutions with cinnamon plant cinnamons, average inhibition diameter (35) mm, nanomaterial with ginger extract, average inhibition diameter (23) mm.